2013
DOI: 10.1038/ncomms2346
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for streptomycin-induced misreading of the genetic code

Abstract: During protein synthesis, the ribosome selects aminoacyl-tRNAs with anticodons matching the mRNA codon present in the A-site of the small ribosomal subunit. The aminoglycoside antibiotic streptomycin disrupts decoding by binding close to the site of codon recognition. Here we use X-ray crystallography to define the impact of streptomycin on the decoding site of the Thermus thermophilus 30S ribosomal subunit in complexes with cognate or near-cognate anticodon stem-loop analogs (ASLs) and mRNA. Our crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
147
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 44 publications
0
147
0
2
Order By: Relevance
“…In contrast, ethanol did not show cooperative synergy with chloramphenicol, which inhibits peptidyl transfer in the ribosome but does not decrease translational accuracy (37), suggesting that ethanol does not impede the peptidyl transfer reaction. These results strongly indicate that sublethal ethanol stress induces physiologically damaging levels of translational misreading, perhaps compromising the conformation of the ribosomal decoding site known to be targeted by streptomycin (38,39).…”
Section: Resultsmentioning
confidence: 80%
“…In contrast, ethanol did not show cooperative synergy with chloramphenicol, which inhibits peptidyl transfer in the ribosome but does not decrease translational accuracy (37), suggesting that ethanol does not impede the peptidyl transfer reaction. These results strongly indicate that sublethal ethanol stress induces physiologically damaging levels of translational misreading, perhaps compromising the conformation of the ribosomal decoding site known to be targeted by streptomycin (38,39).…”
Section: Resultsmentioning
confidence: 80%
“…The inherent plasticity of the decoding site is evident from structural investigations of decoding-site oligonucleotide analogs (Fourmy et al 1996(Fourmy et al , 1998, ribosomes in cognate decoding complexes (Ogle et al 2001;Schmeing et al 2009), and ribosomes in complexes with antibiotics Borovinskaya et al 2008;Stanley et al 2010;Demirci et al 2013) or initiation factor IF1 . The effects of SmD mutations on global aspects of ribosome conformation have been revealed by chemical probing (Allen and Noller 1989) and crystallography (Vila-Sanjurjo et al 2003), but the mechanistic underpinnings of the SmD phenotype remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several biochemical and structural studies have demonstrated that this miscoding occurs at the step of ternary complex (EF-Tu-GTP-amino acid tRNA) binding to the ribosomal A site (2). In the presence of Str, the forward rate constant of the next kinetic step, GTPase activation and hydrolysis, is indistinguishable for both cognate or near-cognate ternary complexes, resulting in reduced accuracy of amino acid-tRNA selection (2)(3)(4).…”
mentioning
confidence: 99%